Analysis of the Fatigue Strength Calculation Method of Crane Reducer - Zhang Zhihong; Liu Zhongming; Wang Zhengbing; Yan Shidang; Zhang Haijun (Jixie chuandong)
The calculation method of equivalent load for crane reducer under variable load condition is analyzed. Application factor formulas for the calculation of gear fatigue strength and bearing fatigue life are deduced,and the index value of the fatigue strength calculation of gear is recalculated based on the life coefficient. In addition,the differences of load spectral coefficients in gear and bearing fatigue calculations are pointed out. The calculation method has a guiding significance for the design and calculation of crane reducer.